A semiconducting polymer nano-prodrug for hypoxia-activated synergetic photodynamic cancer therapy - Cui, Dong (2019)
Photodynamic therapy (PDT) holds great promise for cancer therapy; however, its efficacy is often compromised by tumor hypoxia. Herein, we report the synthesis of a semiconducting polymer nanoprodrug (SPNpd) that not only efficiently generates singlet oxygen (1O2) under NIR photoirradiation but also specifically activates its chemotherapeutic action in hypoxic tumor microenvironment. SPNpd is selfassembled from a amphiphilic polymer brush, which comprises a light-responsive photodynamic backbone grafted with poly(ethylene glycol) and conjugated with a chemodrug through hypoxia-cleavable linkers. The well-defined and compact nanostructure of SPNpd (30 nm) enables accumulation in the tumor of living mice. Owing to these features, SPNpd exerts synergistic photodynamic and chemo-therapy, and effectively inhibits tumor growth in a xenograft tumor mouse model. This study represents the first hypoxia-activatable phototherapeutic polymeric prodrug system with a high potential for cancer therapy.